1993
DOI: 10.1099/00221287-139-11-2865
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bacterial phospholipid markers and plant monosaccharides during forage degradation by Ruminococcus flavefaciens and Fibrobacter succinogenes in co-culture

Abstract: ~~ ~~ ~ ~~~Marker components of the phospholipids of Ruminococcus flavefaciens and Fibrobacter succinogenes were identified for studies on the degradation of forage by these bacteria growing in mixed culture. The principal fatty acid methyl esters and dimethyl acetals detected varied between strains and were influenced by the addition of a mixture of higher volatile fatty acids and vitamins to the medium, but these effects were small compared to the differences between the species. When two strains of R. flave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
4

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 35 publications
(27 reference statements)
5
21
4
Order By: Relevance
“…This observation is consistent with the reported by other researchers (Collings and Yokoyama, 1980; Saluzzi et al, 1993). Studies have also shown that strains of R. flavefaciens have the ability to degrade noncellulosic polysaccharide components of plant cell walls because they produce a variety of other polysaccharidases including xylanase and pectinase (Flint et al, 1989; Erfle and Teather, 1991).…”
Section: Discussionsupporting
confidence: 94%
“…This observation is consistent with the reported by other researchers (Collings and Yokoyama, 1980; Saluzzi et al, 1993). Studies have also shown that strains of R. flavefaciens have the ability to degrade noncellulosic polysaccharide components of plant cell walls because they produce a variety of other polysaccharidases including xylanase and pectinase (Flint et al, 1989; Erfle and Teather, 1991).…”
Section: Discussionsupporting
confidence: 94%
“…Fatty acid analysis of the product recoverd from the phenol phase of OM extract showed the presence of the same fatty acids. No 3-hydroxy acids were detected in either fraction, which agrees with previously published results for fatty acid analysis of F. succinogenes [16].…”
Section: Component Analysis General Characterization and Chemical Desupporting
confidence: 92%
“…The xylanases of F. succinogenes have higher activity than those of ruminococci (Saluzzi et al 1993), and are thought to act to expose cellulose in hemicellulose and/or cellulose complexes. When F. succinogenes S85 is incubated with wheat straw, acetylxylan esterase and arabinofuranosidase activities are also detected at high levels (Matulova et al 2005).…”
Section: F Succinogenes Vs Other Speciesmentioning
confidence: 99%